The Effect of Academic Service Quality on Student Satisfaction Level Stikes Panrita Husada Bulukumba - Tenri Aben; Muriyati; Edison Siringoringo (Comprehensive Health Care, 2022)
Higher education is a form of service provider that involves providers and service users. The quality of a tertiary institution is largely determined by the quality of services provided, such as high achievement motivation, lecturer competence, roles, assignments, and facilities and infrastructure. Good infrastructure is expected to create institutions that are clean, beautiful, and comfortable, so they need to be managed properly. The method used was a descriptive research design with a "cross-sectional" approach. The population in this study were 80 students of the Bachelor of Nursing, D3 Health Analyst, and D3 Midwifery, with a sample size of 43 respondents. The sampling technique used is non-probability with the purposive sampling technique. Data were collected using a questionnaire sheet. Data analysis used Chi-square statistical test. In this study, it was found that the level of student satisfaction with the quality of academic services was not good, indicating that level of student satisfaction was nine respondents (42.9%) dissatisfied and eight respondents (36.4%) satisfied, while good academic service quality showed the level of satisfaction. Fourteen students were satisfied (63.6%), and 12 respondents were dissatisfied (57.1%). Based on the analysis that has been done using the Chi-Square test, there is no influence of the quality of academic services on the level of student satisfaction with a value of p> .451. It is hoped that this research will expand the research sample, not only for students in the VIII and VII semesters but also for other semester students.